Viability Assessment of Allograft Valves by Autoradiography - Khan, Abdul A. (1976)
Autoradiography using [(3)H]thymidine is a quantitative method to assess tissue viability. It has been found to be very useful in the organization of fresh aortic valve allograft banks. A brief description of the technique, as well as the marked difference in the active metabolism of fibro-blasts of valves placed in two storing solutions, is outlined.